Pertumbuhan dan Hasil Kedelai Edamame (Glycine max (L.) Merr.) pada Tanah Gambut yang diberi Dolomit dan Pupuk Hayati: Growth and Yield of Edamame Soybeans (Glycine max (L.) Merr.) on Peat Soils Supplied with Dolomite and Biofertilizer - Asie, Erina Riak; Rumbang, Nyahu; Asie, Kambang Vetrani; Syahrudin, Syahrudin; Darmawan, Darmawan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Edamame soybeans are soybeans that are harvested young so they are known as green soybeans. The high nutritional content and delicious taste make edamame soybeans popular with the public, so they have the potential to be developed. One effort to increase edamame production is through expanding the planting area (Extensification). One type of soil that has the potential for expanding edamame soybean plants is peat soil. This research aims to examine the effect of dolomite and biofertilizer on the growth and yield of edamame on peat soil. The experiment was carried out using a two-factor factorial Completely Randomized Design (CRD) with three replications. The first factor, namely dolomite (0, 5, 10, 15 t ha-1) and the second factor, namely biofertilizer (0, 5, 10, 15 g kg-1 seed). The research results showed that the interaction between dolomite and biofertilizer and the single factor of biofertilizer had no significant effect on the growth and yield of edamame soybeans. Theresults showed that the interaction between dolomite and biofertilizer and the single factor of biofertilizer had no significant effect on the growth and yield of edamame soybeans. The application of dolomite can increase leaf area, plant dry weight, number of pods, and fresh pod weight plant-1 of edamame soybean plants on peat soil. Keywords: extensification, edamame, dolomite, biofertilizer, peat soil